The influence of larval competition on Brazilian Wolbachia-infected Aedes aegypti mosquitoes - Dutra, Heverton Leandro Carneiro (Parasit Vectors, 2016)
BACKGROUND: With field releases starting in Brazil, particular interest must be given to understanding how the endosymbiotic bacterium Wolbachia pipientis affects Aedes aegypti mosquitoes with a Brazilian genetic background. Currently, there is limited information on how the bacterium affects phenotypic traits such as larval development rate, metabolic reserves and morphometric parameters in Ae. aegypti. Here, we analyze for the first time, the effect of Wolbachia on these key phenotypes and consider how this might impact the potential of the bacterium as a disease control agent in Brazil. METHODS: We examined the influence of the wMel strain of Wolbachia in laboratory Ae. aegypti with a Brazilian genetic background, reared under different larval densities. Pupae formation was counted daily to assess differences in development rates. Levels of metabolic reserves and morphometric parameters were assessed in adults resulting from each larval condition. RESULTS: wMel infection led to more rapid larval development at higher densities for both males and females, with no effect under less crowded conditions in females. Infection also led to reduced body size at both high and low density, but not at intermediate density, although the scale of this difference was maintained regardless of larval density, in comparison to uninfected individuals. Wing shape also varied significantly between infected and uninfected mosquitoes due to larval density. Glycogen levels in uninfected mosquitoes decreased under higher larval density, but were consistently high with Wolbachia infection, regardless of larval density. CONCLUSIONS: We demonstrate that the wMel Wolbachia strain can positively influence some important host fitness traits, and that this interaction is directly linked to the conditions in which the host is reared. Combined with previously published data, these results suggest that this Wolbachia strain could be successfully used as part of the Eliminate Dengue Program in Brazil. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13071-016-1559-5) contains supplementary material, which is available to authorized users.